The Law of Obeying A Leader According to the Views of Abu Muhammad Al-Maqdisi Reviewed from Fiqh Siyasah - Misdin Arifin HM; Dirja Hasugian (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
It has become an agreement among Sunni scholars that obeying the leader of the state is an obligation. The obligation to obey this applies to every Muslim leader whether he is cautious or not while not yet falling into real kufr. No one sneaks in this principle except the Khawarij and Mu'tazilah. But there is a figure named Abu Muhammad Al-Maqdisi who in principle has the same understanding as the Sunni scholars in the matter of the obligation to obey the leader even though they are acting arbitrarily against the people. The problem is that there is a statement from al-Maqdisi that shows the fall of the obligation to obey the leaders now, as if Muslim leaders have now apostatized from Islam so that they must not be obeyed or be loyal to them and are even obliged to fight. The formulation of the problem is: (1) how al-Maqdisi's views on obedience to the leader, (2) how the ulama's response to al-Maqdisi's views, (3) What is al-Maqdisi's view according to siyasah fiqh. This study aims to describe and describe the ai-Maqdisi thinking systematically. From this study it can be concluded that al-Maqdisi saw no adherence to the leaders of the Islamic world now because they had apostatized due to abandoning Islamic laws, therefore obliged to fight them according to their respective abilities. Many scholars opposed Al-Maqdisi's ideas but many supported them. However, if viewed from the perspective of the Siyasah fiqh, al-Maqdisi's thinking is incorrect, even very dangerous because it will cause a war between the government and the people so that the country will be chaotic.